2020
DOI: 10.1002/pmrj.12351
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Prosthesis Use in Veterans with Major Upper Limb Amputation: Comparisons by Gender

Abstract: Background A better understanding of women veterans with upper limb amputation is needed. Objective To compare prosthetic use and outcomes of female and male veterans with upper limb amputation. Design Cross‐sectional survey: Amputation characteristics, prosthesis use, and quality of life outcomes were compared by gender. Separate logistic regression models examined association of gender with prosthesis use and receipt of training to use a prosthesis. Separate linear regression models examined the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…A recent study of Veterans with upper limb amputation collected detailed data on prosthesis satisfaction. Results about satisfaction with prostheses, comparing satisfaction ratings of persons with unilateral and bilateral amputation, 15 and device satisfaction by gender 16 have been reported. However, these studies have not compared satisfaction by prosthesis configuration or examined the relationship between initial prosthesis training and device satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of Veterans with upper limb amputation collected detailed data on prosthesis satisfaction. Results about satisfaction with prostheses, comparing satisfaction ratings of persons with unilateral and bilateral amputation, 15 and device satisfaction by gender 16 have been reported. However, these studies have not compared satisfaction by prosthesis configuration or examined the relationship between initial prosthesis training and device satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…2,19,21,25 The prosthesis-related reasons for never using or abandoning a prosthesis can also vary by gender, amputation type, amputation level, and prosthesis type. 28 Prosthesis weight, comfort, and cosmetic appearance tend to be higher priorities for women, whereas prosthesis functionality and durability have been found to be of greater importance to men. 30 Prosthesis fit and cosmetic appearance also tend to be of greater importance in those with ULA.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In addition, lower prosthesis satisfaction ratings, female gender, upper-limb body-powered prosthesis type, lower baseline prosthesis use, vascular amputation etiology, cardiac conditions, and issues involving the remaining limb have all been associated with higher rates of prosthesis abandonment. 18,22,26,[28][29][30] Prior studies involving veterans with both ULA and LLA found higher rates of prosthesis abandonment in Vietnam-era veterans, who are older, compared with veterans who served in Iraq and Afghanistan after 2001, 18,24 whereas other studies have reported an inconsistent association between increased age and prosthesis nonuse. 2,22 Prosthesis discontinuation most commonly results from issues related to either prosthesis comfort or functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, repeated excessive upper body movements generate early fatigue and pain which naturally leads to overuse of the intact limb 4 , 5 . Multiple survey studies indicate that the dissatisfaction factor of upper limb prostheses has been attributed to limited function, control strategy, and having higher weight 6 9 . Especially to increase the functionality of the prosthetic devices, state-of-the-art prosthetic designs have been developed to restore lost limb functions with multiple active degrees of freedom (DoF) 10 12 .…”
Section: Introductionmentioning
confidence: 99%